THE INFLUENCE OF COMPETENCY AND WORK CULTURE ON WORK MOTIVATION AND ITS IMPLICATIONS ON EMPLOYEE PERFORMANCE AT PT. ERAGUNA BUMI NUSA JAMBI BRANCH - Eko Yuwono, Sigit (Yayasan Pendidikan Cahaya Budaya Indonesia, 2025)
Effective utilization of human resources is key to organizational sustainability. This study examines the HR development strategy at PT. Eraguna Bumi Nusa, Jambi City Branch, to improve employee performance through increased competency and work culture mediated by work motivation. The analysis uses an HR management framework with a cross-sectional approach to 36 respondents through a multilevel regression test. The method used in this study uses a quantitative method with statistical calculation techniques. The results show that competency and work culture have a positive and significant effect on work motivation, which in turn improves employee performance.